DAYA TAHAN ALAMI 30 JENIS KAYU TERHADAP RA YAP TANAH Macrotermes gilvus (Hagen); SUATU UJI LAPANG YANG DIPERCEPAT - Paimin Sukartana (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
Two bundles of wood samples consisting of each thirty wood species were exposed to subterranean termite Macrotermes gilvus (Hagen) for 14 weeks (3.5 months) in a rural area of Cikampek and in an arboretum of the Centre for Forest and Natural Conservation Research and Development located in Janlapa, Bogor. To accelerate the termite attack, a piece of corru- gated paper was inserted in each layer of wood arrangements in the bundles. in Cikampek, the wood samples were directly exposed to an active colony of the termite species. Meanwhile, in Jalanpa such test method was not conducted because the experiment formerly was not designated to this termite species. Thus, the attack by this termite species was probably occured by chance only.the result of the experiment showed that, excepl the damage degree, there was no significant difference in the pauern of termite attack between the test samples exposed in the two locations. Here, most stake tests exposed in Cikampek were more severely infested than those in Jalanpa. From the two test sites, it can be concluded that aboui 37% (Aglaia versteeghii , Hopea odorata, Khaya anthothcca, Mimusop elingi, Neonauclea spec, Planchonia valida, Quercus turbinata, Eucalyptus urophylla, Eugenia lincata, E. polyantha, and Podocarpus blumei, 13% (Altingia excelsa, Castanopsis javanica, Shorea seminis, Swintonia glauca), 20% (Calophyllum inophyllum, Dacrydium becarii, Gluta walichii, Heritiera javanica, Peronema canescens, and Shorea platy- clados), 23 % (Agathis philippinensis, Anthocephalus cadamba, Anthocephalus spec., Eucalyptus alba, Gluta renghas, G, rostrata, Shorea meristopteryx.), and 7 % (Elaeocarpus sphaericus; Laplacea subintegerrima) might be respectively classified highly resistant, resistant, moderately resistant, less resistant, and perishable to the termite attack.